Peritoneal Tuberculosis in a Patient with Chronic Myeloid Leukemia and Diabetes Mellitus: A Diagnostic Dilemma - Bhuian, Tareq Mahmud; Rahman, Md. Mahbubur; Hoque, Md. Nazmul; Rahim, Muhammad Abdur; Rahman, Md. Motiur; Rahman, Md. Anisur (BIRDEM Medical Journal, 2013)
Tuberculosis (TB) may complicate patients with chronic myeloid leukaemia (CML) receiving imatinib mesylate, but concomitant diagnosis of TB and CML is rare. Here, we present a middle aged Bangladeshi diabetic lady who got admitted because of prolonged pyrexia, ascites and splenomegaly. Diagnostic workup confirmed peritoneal TB and CML. Being an uncommon entity, we are reporting the case. Birdem Med J 2013; 3(2): 113-115 DOI: http://dx.doi.org/10.3329/birdem.v3i2.17217